A Pragmatic Realization of Humor in Selected Physician-Patient Speech - Asst. Inst. Jinan Kadhim Ismaeel (Journal of College of Education, 2025)
Linguistically, features such as puns, irony, sarcasm, wit, and contrastive utterances often contribute to the complex concept of humor that people associate with communication. Humor involves not only linguistic elements but also extralinguistic factors that shape how it is delivered and perceived. Paul Grice (1975) proposed four cooperative principles—maxims of quantity, quality, relevance, and manner—that govern successful communication. However, Attardo (1990) argues that violating these maxims is a common phenomenon in humorous discourse. This study aims to analyse physician-patient conversational extracts through a linguistic pragmatic lens, using the classification system from Wit and Humor in Discourse Processing. It explores the mechanisms by which violations of Gricean maxims contribute to the creation of humor. The research adopts a qualitative approach, focusing on two levels of analysis: the pragmatic realization of humor and the violation of Gricean maxims. Findings indicate that the most frequently violated maxims in the selected extracts are the maxims of quality and manner. Furthermore, irony emerges as the most prevalent pragmatic mechanism used to generate humor through these violations. This study provides insights into the interplay between linguistic pragmatics and humor in medical communication contexts.
Keywords: Pragmatics and Gricean maxims, Pragmatics and Humor, Humor and Clinical Setting.